2013
DOI: 10.1055/s-0033-1356194
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Contrast-Enhanced Ultrasound with Two Distinct Types of Blood Vessels for the Assessment of Angiogenesis in Lewis Lung Carcinoma

Abstract: The study showed that among the distinct types of vasculature (CD31 + and CD34 +) in Lewis lung carcinoma, the former correlated with the CEUS parameters. Therefore, CEUS using a second-generation US contrast agent may be useful for the evaluation of tumor angiogenesis of LLC of mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 6 publications
0
10
2
Order By: Relevance
“…CD31 is expressed in both undifferentiated and differentiated endothelial cells, 55 and may thus reflect the complete profile of synovial neovascularization. PDUS only detected blood flow signals in vessels >100 µm, 34 while CEUS with SonoVue detected synovial vessels <50 µm. 34 Moreover, ultrasound contrast agents are less likely to leak into the synovial fluid than magnetic resonance imaging contrast agents, thus providing a more accurate reflection of synovial and vascular changes in the joint.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…CD31 is expressed in both undifferentiated and differentiated endothelial cells, 55 and may thus reflect the complete profile of synovial neovascularization. PDUS only detected blood flow signals in vessels >100 µm, 34 while CEUS with SonoVue detected synovial vessels <50 µm. 34 Moreover, ultrasound contrast agents are less likely to leak into the synovial fluid than magnetic resonance imaging contrast agents, thus providing a more accurate reflection of synovial and vascular changes in the joint.…”
Section: Discussionmentioning
confidence: 96%
“…PDUS only detected blood flow signals in vessels >100 µm, 34 while CEUS with SonoVue detected synovial vessels <50 µm. 34 Moreover, ultrasound contrast agents are less likely to leak into the synovial fluid than magnetic resonance imaging contrast agents, thus providing a more accurate reflection of synovial and vascular changes in the joint. 56 CEUS thus increases the possibility of identifying patients with latent but progressive RA based on the good association between CEUS findings and hypervascularization.…”
Section: Discussionmentioning
confidence: 96%
“…This suggests that PDI has limited sensitivity for detect neovascularization during early-stage disease. This is likely because PDI can only detect blood flow signals in vessels with diameters greater than 100 µm [7], and synovial neovascularization during early-stage disease is mainly in the capillaries. This interpretation is consistent with our pathological examinations of synovial tissues during early-stage disease.…”
Section: Ceus Imagingmentioning
confidence: 99%
“…Many studies have confirmed that power Doppler imaging (PDI) can detect pannus neovascularization [5,6], and this technique is an important method used to assess the activity of RA and evaluate the effects of different therapies. Real-time gray-scale ultrasound (US) using the SonoVue contrast agent improves the ability to detect blood vessels as small as capillaries (< 50 µm) [7], and provides measurements of hemodynamic parameters that can be used for quantitative analysis. However, no previous studies have used US to determine longitudinal changes in vascularization during the progression of RA.…”
Section: Introductionmentioning
confidence: 99%
“…Contrast-enhanced ultrasonography (CEUS) of the tumor vasculature in animal models appears to be effective in evaluating tumor vasculature in a non-invasive manner (Forsberg et al 2011;Zhou et al 2011;Zhuo et al 2014). CEUS has been reported to have an effect on the evaluation of microvascular morphology and angiogenesis in HCC (Hatanaka et al 2010;Schacherer et al 2010;Xiao et al 2010;Zheng et al 2013).…”
Section: Introductionmentioning
confidence: 99%